2014
DOI: 10.1111/evo.12380
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Genetic Modeling and Inference in the Presence of Nonignorable Missing Data

Abstract: Natural selection is typically exerted at some specific life stages. If natural selection takes place before a trait can be measured, using conventional models can cause wrong inference about population parameters. When the missing data process relates to the trait of interest, a valid inference requires explicit modeling of the missing process. We propose a joint modeling approach, a shared parameter model, to account for nonrandom missing data. It consists of an animal model for the phenotypic data and a log… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
37
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 36 publications
0
37
0
Order By: Relevance
“…In our study, viability was the missing data process, as well as the focus of our investigations, hence viability selection was explicitly considered in our genetic analyses. For traits with low heritability, such as in our study (heritability , 0.25 for all traits), the bias in univaritate estimates of genetic variation caused by ignoring the missing data process can be relatively small [51]. However, our data and the field data of Steinsland et al [51] demonstrate that the genetic covariance associated with viability can be large.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…In our study, viability was the missing data process, as well as the focus of our investigations, hence viability selection was explicitly considered in our genetic analyses. For traits with low heritability, such as in our study (heritability , 0.25 for all traits), the bias in univaritate estimates of genetic variation caused by ignoring the missing data process can be relatively small [51]. However, our data and the field data of Steinsland et al [51] demonstrate that the genetic covariance associated with viability can be large.…”
Section: Discussionmentioning
confidence: 49%
“…For example, Mojica & Kelly [52] found that estimates of selection on flower size in Mimulus guttatus changed sign when the negative association between flower size and survival to maturity was included in their analyses. Similarly, Hadfield [50] and Steinsland et al [51] show that ignoring missing data when data are not missing at random can bias estimates of predicted breeding values and additive genetic variation. In our study, viability was the missing data process, as well as the focus of our investigations, hence viability selection was explicitly considered in our genetic analyses.…”
Section: Discussionmentioning
confidence: 99%
“…genes passed on by the mother have different effects than when passed on by the father, Lawson et al ., ), which can also depend on offspring sex (the parent‐of‐offspring effect may differ between sons and daughters, Hager et al ., ). From an ultimate point of view, the sex‐specific association between sleep and plumage spottiness is in line with recent results showing that selection acting on this plumage trait is sex specific (Roulin et al ., ,b, ; Steinsland et al ., ). Selection on spottiness is positive in females but negative in males, implying that physiological traits such as sleep could be associated with plumage spottiness in a sex‐specific way as reported in the present study.…”
Section: Discussionmentioning
confidence: 97%
“…; Charmantier and Reale ; Hadfield ) and problems arising from missing data (e.g., Steinsland et al. ; Wolak and Reid ). In contrast, although known for a long time (e.g., Price and Boag ), the effects of phenotypic measurement error on estimates of (co‐)variance components have received less attention (but see, e.g., Hoffmann ; Dohm ; Macgregor et al.…”
mentioning
confidence: 99%